The Greeks and the Secret War among Venice, Spain and the Ottoman Empire: the Plans for the Occupation of Nafplio - Kostas G. Tsiknakis (Nuova Antologia Militare, 2022)
The occupation of Nafplio by the Ottomans during the Third Venetian–Ottoman War (1537–1540), intercepted a long period of Venetian rule over the city. In the next few years, the reconquest of the city remained among the prime goals of the Venetian policy. Discussions were intensified on the eve of the Fourth Venetian–Ottoman War (1570–1573). Secret agents from both the Venetian and Spanish sides, who toured the Ottoman-occupied Greek territory, collected detailed information about the state of the fortress so as to seek ways for its siege and occupation. Such a possibility, as planned, would trigger general developments and would result in the release of the entire Peloponnese. During the War, however, the forces of the Christian fleet undertook no serious attack against Nafplio. This negative development was due to disputes arisen in the meantime between Venice and Spain concerning their presence in the East.